Pengorganisasian Program Penyakit Tidak Menular (PTM) di Puskesmas Tambang Kabupaten Kampar Tahun 2019 - Nefi Asmareni; Kiswanto Kiswanto; Ahmad Hanafi (Jurnal Kesehatan Komunitas, 2021)
ABSTRACT Organazing is a process pf detemining, grouping and managing various activities needed to achieve goals. One of the Health District Office programs ie the Prevention and Control for Non-Communicable Diseases (NCDs) program. Tambang Primary Health Care is one of 31 Primary Health Care in Kampar District Government which alredy has an organizing Non-Communicable Diseases (NCDs). This research aims to find out the organazing of the Non-Communicable Diseases program (NCDs) at the Tambang Primary Health care. This research was conducted in May-June 2019. This research is a qualitative study. Data was collected through in-depth interviews, observation and document review. The number of informants in this study were 8 people. The results of the study show that the division of work description has already done. Departementalisasi of work has been done based on the type of region, type of customer and type of activities even though it is already. Organization relationship has run according to the hierarchy level. Coordination has not run optimally. The head of the Primary Health Care has diving the tasks in detail in detail such as work guidelines, workload analysis, determine the human resource requirements and improve the inter-health district office meetings for achieving program objectives. Keywords : Organizing, Non-Communicable Diseases